Online Portfolio Assessment, Formative Assessment, and Summative Assessment on Students’ Writing Skills: An Experimental Study - Masrul Masrul; Sri Yuliani (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
The development of online learning in developed countries is advancing, yet in developing countries, the development is still at the early stage. It is necessary to investigate the potentials and the available facilities to support online learning in developing countries, including Indonesia. This study investigated the impacts of online portfolio assessments, formative assessments, and summative assessments on students' writing abilities. An experiment was conducted, involving 115 participants undergraduate students majoring English (60 females and 55 males) at the State University of Malang. All of the participants had passed the “Grammar and Writing I” required course offered in the first semester. The data were collected using single instrument: an electronic writing forum. The main data analysis tools used in this research were the McManemar test and the Cohran test. The results showed that online portfolio assessment, formative assessment, and summative assessment significantly affected students' writing skills. Online portfolio assessment, formative assessment, and summative assessment in essay writing help students develop their writing skill, particularly in terms of grammar and linguistic structure. Significant gaps were found between pre-test and post-test treatments' peer feedback and peer assessment. The two variables positively affected the process of essay writing and the completion of writing assignments of the students.